2016
DOI: 10.11648/j.crj.20160402.11
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anticancer Potential of Water Garlic Extract and Copper in a Human Hepatocarcinoma Cell Line

Abstract: Garlic extract in water, supplemented with copper, exerts an enhanced anti-proliferative and a caspase-independent apoptotic activity in a human hepatocarcinoma HepG2 cancer cell line. Furthermore, a DNA double strand break downstream, likely responsible for the observed cell death in HepG2 cell, was evidenced by an early over expression of p53 and p21. This observed synergistic antiproliferative and antitumor capability of water garlic extract, in the presence of copper, might be useful as new tool in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…In our experiments high concentrations of garlic extract definitely contains a lot of allicin, which could be the explanation of the lack of caspase-3 activity. Similar to our results, De Martino et al (2016) showed that the aqueous garlic extract, supplemented with copper, enhanced anti-proliferative and a caspase-independent apoptotic activity in HepG2 cancer cell line (De Martino et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our experiments high concentrations of garlic extract definitely contains a lot of allicin, which could be the explanation of the lack of caspase-3 activity. Similar to our results, De Martino et al (2016) showed that the aqueous garlic extract, supplemented with copper, enhanced anti-proliferative and a caspase-independent apoptotic activity in HepG2 cancer cell line (De Martino et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…However, authors show that in each of studied cell lines different concentrations of garlic extracts stimulated caspase-3 activity. Moreover, it has also been demonstrated that garlic extracts or garlic components such as allicin or gallic acid cause a caspase-independent cell death (De Martino et al, 2016, Ji et al, 2009, Park et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Antiproliferative effect, overexpression of p53 and p21 (break of DNA strand) [29] Crude garlic Inhibition of cell proliferation [137] Heat-aging Inhibition of cell proliferation [7] SGC-7901 (human gastric cancer) Aged black garlic Inhibition of cell growth through apoptosis, inhibition of tumor growth in rats, which may result from antioxidant and immunomodulating effects [141] AsPC-1 (pancreatic beta cells) Oil…”
Section: Aqueousmentioning
confidence: 99%
“…In a previous paper [1] we reported that water-soluble garlic extracts (GE), supplemented with copper (Cu), exerts an enhanced anti-proliferative and a caspase-independent apoptotic activity in a human hepatocarcinoma HepG2 cancer cell line. The bioavailability of garlic compounds depends on several factors, first of all the method of processing the bulbs to obtain the garlic extract.…”
Section: Introductionmentioning
confidence: 99%